ICT for learning and inclusion in Latin America and Europe - Santana Botana, Lourdes Miriam; Andreu Gómez, Nancy; Bilbao Consuegra, Maida Librada; Martínez Consuegra, Juan Gustavo; Palacios Morales, Carlos Javier; González Peña, Raúl; Llopiz Guerra, Karel (My University, 2020)
Cuba is gradually developing a computerization process of its society, by which all social and economic spheres receive inestimable benefits. The educational sector is revolutionized with the appearance of new technologies for learning. Pedagogy is being improved as new ways of teaching and learning appear with the use of digital resources. Digital inclusion of all groups and sectors that for one reason or another have limitations for access to ICT, is among the main objectives of Cuban society. The present chapter ventures into this issue and systematically exposes achievements, projections and barriers still existing for the gradual digital inclusion of the disabled, elderly, women, children and young people from rural schools in remote areas. Educational experiences that have been obtained are addressed, as well as pedagogical and technological challenges that still need to be resolved in order to reduce the digital divide in Cuba.
Keywords: Cuba, ICT, education, Digital inclusion